Joke structures and politeness strategies in Malaysian stand-up comedy - Chan, Teik Onn (2018)
According to Wilson (2008), stand-up comedy is a form of social criticism on ethnicities and politics other than a means for entertainment, and it can be effective with the correct use of politeness strategies. It also has a specific form of narrative, known as a joke, told by the comedian, as suggested by Attardo and Chabanne (1992). It is also subjected to rhetorical strategies taken by comedians to present their jokes without negative backlash. Therefore, in examining the differences of joke structure between ethnic and political jokes in Malaysia, their usage of politeness strategies and how these strategies were manifested through specific rhetorical devices, Hockett’s (1960) Internal Structure of Jokes, Brown and Levinson’s (1987) Politeness Strategies and Schwarz’s (2010) Rhetorical Devices in Joke-Telling were utilized as frameworks for the study. The findings revealed that the joke structure in political jokes lack buildups to specify the topic. Ethnic jokes, on the other hand, often targeted specific aspects of an ethnicity with build-ups. In the use of politeness strategies, off-record strategy was dominantly used in both ethnic (32.3%) and political jokes (56.66%) to veil their face threats. The least used strategy in ethnic jokes is positive politeness (18.5%) and in political jokes, negative politeness (10%). In rhetorical devices, ethnic jokes relied on implication in their use of off-record strategy, whereas profanity remains unused. In political jokes, however, the dependence on implication, private ridicule was another rhetorical device that was dominantly used, while hyperbole and ridicule were unused. In conclusion, political jokes tend to omit build-up to make the topic of discussion more ambiguous whereas ethnic jokes use build-up to specify a stereotype to avoid making fun of an ethnicity in its entirety. In addition, off-record strategy is most effective in both types of jokes because it allows engagement from audiences in deciphering the joke, making face threats less direct. This strategy was often accompanied with the use of implication and private ridicule. With these findings, it is hoped that the results will create awareness among aspiring comedians on the use of politeness strategies in their joke delivery. Furthermore, the results may provide useful resources for aspiring comedians and public speakers to introduce humour without creating negative backlash.